Production of cartilage degrading activity by human synovial tissues. - Brown, M F (1987)
Human synovial tissues have been assayed for the production of cartilage degrading activity (CDA). This activity is thought to be homologous with catabolin/interleukin 1 (IL1) produced by porcine synovium and leucocytes and by human leucocytes. The CDA of 26 rheumatoid (RA) and 41 non-rheumatoid synovia was measured on a dry weight basis. The rheumatoid synovia showed a threefold increase in activity over the non-rheumatoid, but there was no significant overall difference on a deoxyribonucleic acid (DNA) basis. The rheumatoid synovia appeared to consist of two populations; in over half the samples CDA was not related to cellularity, but eight patients had a high CDA and a high cellularity.